DESCRIPTION OF THE RHEUMATOID FACTOR TEST IN WOMEN THE MENOPAUSE TO DETECT RHEUMATOID ARTHRITIS IN ULAPATO-A VILLAGE, GORONTALO DISTRICT - pratiwi dunggio; Titin Dunggio; Rita Amini Warastuti (LPPM Universitas Bina Mandiri Gorontalo, 2021)
Based on data from the Gorontalo provincial health office in 2017 the incidence of Rheumatoid Arthritis reached 14,391 the number of cases. Rheumatoid Arthritis is a chronic autoimmune inflammatory system disease whose cause is unknown. Symptoms of Rheumatoid Arthritis include experiencing stiffness in the joints in the morning, and swelling of the joints. This study aims to determine the results of Rheumatoid Arthritis test in menopausal women in Ulapato-A Village, Gorontalo District by examining Rheumatoid Factors. This research is a quantitative descriptive study with a total of 34 samples. Using manual Rheumatoid Factor Check. This research was processed through the IBM SPSS Statistics V25.0 program. then presented in tabular form and reported as a percentage using the Frequency Distribution formula. From the results obtained, 8 samples (23.5%) were positive while 26 samples (76.5%) were negative. In conclusion Rheumatoid factor in menopausal women is mostly negative. It is hoped that Rheumatoid Arthritis sufferers maintain their health by living a healthy lifestyle and doing light exercise and for other researchers to also carry out semi-quantitative follow-up examinations if they get a positive sample.